A GIS-Based DRASTIC Model For Assessing Aquifer Vulnerability - Sedigheh Anvari; Mohammad Rezakhani Nejad (علوم و مهندسی آبیاری, 2022)
Due to the increasing demand for water resources in agricultural, domestic, and industrial sectors, the quality of groundwater resources in Iran is at risk. This is more sensitive for the arid and semi-arid regions of the country where the main supply of water is from groundwater resources. The aim of this study was to investigate the vulnerability of the groundwater aquifer of Sirjan Plain (Kerman province). For this purpose, the DRASTIC model was employed, while the Geographical Information System (GIS) software was used to draw the vulnerability map. In the DRASTIC model, the effective characteristics in assessing the vulnerability of groundwater aquifers including water table depth, net recharge, aquifer type, soil type, topographic slope, the media forming the vadose zone, and hydraulic conductivity were used. They were prepared in seven layers in the ArcMap software and by weighing, ranking, and combining these layers, the final vulnerability map of Sirjan Plain with respect to contamination was produced. The results showed that the DRASTIC index for the mentioned plain was between 69 and 141 and that the southern parts of this plain were more susceptible to contamination. Moreover, the investigation of the nitrate ion on the final DRASTIC map showed that all the points with high nitrate content were in the highly contaminated zone. This can confirm the accuracy of the model.